Sistem Pakar Diagnosis Gangguan Tumbuh Kembang Balita Menggunakan Metode Forward Chaining Berbasis Web - Izhar Suhanda , Eka; Lanang Putra Eka Prismana , I Gusti (Inovate, 2023)
Errors in understanding the growth and development of toddlers that are not in accordance with medical procedures can result in delays in the process of growth and development of a toddler. Not all parents understand growth and development disorders, parents prefer to entrust their toddler's examination to a pediatrician. But with the convenience of a pediatrician, doctors sometimes have limited hours of practice and parents have to spend a budget to have their toddler checked. So that parents need more computer systems that can diagnose diseases with doctor's recommendations and do not need to come directly to the children's hospital. A computer system that can diagnose disease is an expert system, an expert system provides a knowledge base and solutions for a disease. Expert systems have many methods that can diagnose disease, including the forward chaining method. The forward chaining method will run from a fact that is implemented with the IF and Then sections, then through rules that contain symptoms and disease diagnoses, then the method produces a disease diagnosis and its treatment. This system obtained accuracy with pediatricians by 80% with an assessment of the system being used effectively. Keywords: Developmental Disorders, Forward Chaining, Diagnosis, Accuracy